(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Enzyme-linked immunosorbent assay (ELISA) is a laboratory immunological method for the qualitative or quantitative determination of various low molecular weight compounds, macromolecules, viruses, etc., based on the specific reaction of antigens (AG) with antibodies (AT). The detection of the resulting complex is performed using an enzyme as a label to visualize the reaction.